Two unusual neuro-psychiatric manifestations of malaria in a tertiary care hospital: a review of literature - Roy, Manoj Kumar; Dutta, Joydip; Chatterjee, Apratim; Sarkar, Anup; Roy, Koushik; Mukhopadhyay, Sumanto; Mukhopadhyay, Jotideb (International Journal of Research in Medical Sciences, 2017)
Malaria, a highly prevalent parasitic disease in tropical country, have some atypical neuro-psychiatric manifestations seen in both vivax and falciparum malaria. We are reporting two cases of unusual neuro-psychiatric manifestations of malaria admitted in our hospital, one with intralobar haemorrhage and other with atypical psychiatric features. The rarity of the presentation has been highlighted with possible pathogenesis discussed after literature review.